Pengaruh Brand Ambassador, Citra Merek dan Harga terhadap Keputusan Pembelian Produk Skincare Scarlett pada Masyarakat di Yogyakarta - Laura Sri Rejeki; Sri Ekanti Sabardini (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2023)
This research aims to determine the influence of Brand Ambassador, Brand Image and Price on purchasing decisions for Scarlett Whitening brand skincare products. This research is a quantitative research conducted on Scarlett skincare consumers in Yogyakarta who are consumers of Scarlett products, a total of 75 people. Data were analyzed using multiple linear regression tests. Based on the results of data analysis, the results obtained were that Brand Ambassador had a significant positive effect on purchasing decisions with a significance value of 0.016 and a regression coefficient of 0.369. Brand image has a significant positive effect on purchasing decisions with a significance value of 0.021 and a regression coefficient value of 0.328. Price has a significant positive effect on purchasing decisions with a significance value of 0.01 and a regression coefficient value of 0.417. The coefficient of determination value shows that Brand Ambassador, Brand Image and Price have an influence of 72.6% on purchasing decisions.